2014
DOI: 10.1186/1471-2407-14-42
|View full text |Cite
|
Sign up to set email alerts
|

A longitudinal analysis of patient satisfaction with care and quality of life in ambulatory oncology based on the OUT-PATSAT35 questionnaire

Abstract: BackgroundIn the oncology setting, there has been increasing interest in evaluating treatment outcomes in terms of quality of life and patient satisfaction. The aim of our study was to investigate the determinants of patient satisfaction, especially the relationship between quality of life and satisfaction with care and their changes over time, in curative treatment of cancer outpatients.MethodsPatients undergoing ambulatory chemotherapy or radiotherapy in two centers in France were invited to complete the OUT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
63
0
3

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 50 publications
(75 citation statements)
references
References 42 publications
9
63
0
3
Order By: Relevance
“…This finding supports some earlier findings (Pini et al., ) but contradicts many others (e.g., Arraras et al., ; Ejaz et al., ; John et al., ; Wessels et al., ). Previous studies have suggested that perceived health status is associated with patients' assessments of quality care attributes (Brennan et al., ; Nguyen et al., ; Tremblay et al., ) and age (Browall et al., ; John et al., ). After the split of the data into the two age‐related subgroups, the subsequent analysis showed clear associations, within both groups, between patients' assessments of quality‐of‐care attributes and perceived health status.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding supports some earlier findings (Pini et al., ) but contradicts many others (e.g., Arraras et al., ; Ejaz et al., ; John et al., ; Wessels et al., ). Previous studies have suggested that perceived health status is associated with patients' assessments of quality care attributes (Brennan et al., ; Nguyen et al., ; Tremblay et al., ) and age (Browall et al., ; John et al., ). After the split of the data into the two age‐related subgroups, the subsequent analysis showed clear associations, within both groups, between patients' assessments of quality‐of‐care attributes and perceived health status.…”
Section: Discussionmentioning
confidence: 99%
“…In a third study, Nguyen et al. () found that self‐evaluated global health was the major determinant of patient satisfaction with care.…”
Section: Introductionmentioning
confidence: 99%
“…30 Several studies have shown that cancer patients often are dissatisfied with the type and amount of information provided. 14, [16][17][18] In 2016, the Danish government launched several improvement initiatives aimed at improving the patient experience of cancer care. 6,7,9,11,12,15,29,31,32 In high-performing health care organizations, there is an increased focus on providing patient-centered care, including giving more consideration to the patients' needs and wishes and emphasizing shared-decision making.…”
Section: Findings In the Literaturementioning
confidence: 99%
“…2,3 Satisfied patients report higher quality of life and are more likely to comply with treatment and continue their use of medical services, which may lead to improved clinical outcome. [14][15][16][17][18] Other aspects that have been significantly associated with overall rating of care are the physical settings of the health care center, such as cleanliness and comfort, 8,17 as well as patient characteristics, such as age, 7,10,12,13,16,19,20 sex, 6,21,22 cancer diagnosis, 12,[22][23][24] education level, 10,12,20,22 self-perceived health status, 10,16,17 and metastasis. [6][7][8][9] Findings include aspects relating to the coordination of care, 10 information, 3,6,11,12 waiting times, 3,13 and interpersonal relationships between health care personnel and patients.…”
Section: Introductionmentioning
confidence: 99%
“…Besides social functioning, more severe pretreatment neurological deficits of the arms or legs were also associated with dissatisfaction after surgery and/or radiotherapy. Neurological deficits have a debilitating effect on HRQOL and functional status; therefore, these patients may have had higher expectations of the functional outcomes and could be harder to satisfy …”
Section: Discussionmentioning
confidence: 99%